Cardio-metabolic profile of subjects with early stages of glucose intolerance and cardiovascular autonomic dysfunction - Dimova, Rumyana; Tankova, Tsvetalina; Chakarova, Nevena; Grozeva, Greta; Dakovska, Lilia (Diabetes research and clinical practice, 2017)
•There is a rather high prevalence of cardio-vascular autonomic dysfunction in the early stages of glucose intolerance.•Age, HbA1c, QTc interval and presence of arterial hypertension are related to the presence of CAD in this population.•Novel screening algorithms are needed to determine high risk populations. The present study evaluates the cardio-metabolic profile of subjects with early stages of glucose intolerance and presence of cardiovascular autonomic dysfunction (CAD). 478 subjects, of mean age 49.3±13.7years and mean BMI 31.0±6.2kg/m2, divided according to glucose tolerance: 130 with normal glucose tolerance, 227 with prediabetes, and 121 with newly-diagnosed type 2 diabetes, were enrolled. Glucose tolerance was studied during OGTT applying 2006 WHO criteria. Anthropometric indices, blood pressure, HbA1c, serum lipids, hsCRP, and albumin-to-creatinine ratio (ACR) were measured. Body fat distribution was estimated by a bioimpedance method (InBody720, BioSpace). Tissue AGEs accumulation was assessed by skin autofluorescence (AGE-Reader-DiagnOptics™). CAD was assessed by ANX-3.0 method. CAD was found in 24.1% of subjects with any disorder of glucose tolerance in comparison to 12.3% in NGT, OR 2.0 (95% CI: 1.2–3.2), p=0.005. Sympathetic and parasympathetic tone declined with the progression of glucose intolerance. Age, waist circumference, visceral fat area, fasting and 120-min plasma glucose, HbA1c, AGEs, ACR and QTc interval were higher in subjects with CAD, p<0.05. In a logistic regression analysis the panel of age >53years (76% sensitivity, 61% specificity), HbA1c >6.0% (66% sensitivity, 60% specificity), QTc interval >423ms (65% sensitivity, 61% specificity) and presence of arterial hypertension (83% sensitivity, 55% specificity) was related to the presence of CAD – AUC 0.778 (95% CI: 0.73–0.83), p<0.001. Our results demonstrate a high prevalence of CAD in early stages of glucose dysmetabolism. Age, HbA1c, QTc interval and presence of arterial hypertension are related to the presence of CAD in this population.